On Solving Bottleneck Bi-Criteria Fuzzy Transportation Problems - E. Sobana, V.; Anuradha, D.; ., . (International Journal of Engineering and Technology, 2018)
A fuzzy blockâ€“dripping method (FBDM) has been proposed to find the best compromise solution and efficient solutions of the bottleneck bi-criteria transportation problem under uncertainty. The procedure of the proposed method is illustrated by numerical example.Â